if f:R->[pi/6,pi/2),f(x)= arcsin (x^2 - a/x^2 + 1) is a onto function,den set of values of "a" is.....

3 years ago

Share

Answers : (1)

                                        
Ans:
y = sin^{-1}(x^{2}-\frac{a}{x^{2}}+1)
(x^{2}-\frac{a}{x^{2}}+1)=siny
x^{4}+(1-siny)x^{2}-a=0
This is simple Quadratic in x2,
\Delta \geq 0
(1-siny)^{2}\geq 4.(-a)
sin^{2}y-2siny+1+4a\geq 0
\Delta <0
4<4(4a+1)
a>0
Thanks & Regards
Jitender Singh
IIT Delhi
askIITians Faculty
7 months ago

Post Your Answer

More Questions On Differential Calculus

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
find dy/dx when y= (sin^-1 (x))^x + x^x
 
 
Ans: Hello Student, Please find answer to your question below Now simply apply the chain rule
  img
Jitender Singh 6 months ago
Let f : A-> A where A = { 1, 2, 3, 4, 5} such that ff(x) = x . How many such functions are possible
 
 
First note that the function is injective: f(x) = f(y) implies f(f(x)) = f(f(y)) which yields x = y. We say that a number x is fixed by f if f(x) = x. Now, if f(a) = b, with a and b unequal,...
 
mycroft holmes 4 months ago
 
In general the real functions which satisfies the condition that fof(x) = x are (i) f(x) = a – x where a is any real no. (ii) f(x) = x But here, f: A → A is the function which should satisfy...
 
Y RAJYALAKSHMI 4 months ago
 
Pl. ignore this solution – it is incomplete
 
Y RAJYALAKSHMI 4 months ago
Prove that
 
 
let y = f(x) g(x) Taking log on both sides log y= g(x) log(f(x)) Taking antilog on both sides y = e g(x) logf(x) Consider log f(x)= log ( 1 + (f(x)-1)) Expansion of log ( 1 + x)= x – x...
  img
Harsh Patodia 3 months ago
 
Hi Student, Basically subtraction of 1 comes from the derivation. So it must be done. If you want to know the derivation please reply on this thread otherwise its not necessary. You can...
  img
Harsh Patodia 3 months ago
 
Hi student This is of the type f(x) g(x) which is of form 1 such that f(x) 1 and g(x) Solution of such form is give by e g(x)(f(x)-1) When you will subsitute appropriate values of f(x) and...
  img
Harsh Patodia 3 months ago
∫x 2 sin 3 x dx
 
 
Obtain the integration of Sin 3 x from the Sin3x equality involving Sin 3 x in terms of Sinx and Sin 3x. Now, for∫x 2 sin 3 x dx, use by parts (with ILATE: Inverse, log, algebraic, Trig,...
  img
Ravi 2 months ago
1∫ -1 ( x + 3) dx
 
 
integration of x+3 from -1 to 1 is equal to (((x^2)/2)+3x) from -1 to 1 ((1/2)+(3))-((1/2)-3) =3+3 =6
 
Miryala Gopalakrishna 3 months ago
 
Ans:- 1 ∫ -1 (x+3)dx =[(x 2 /2)+3x] -1 1 =[(1 2 )/2 -(-1 2 )/2]+3(1-(-1)) =(1/2)-(1/2)+6 =6
 
Anusha 3 months ago
In a triangle root(abc(a+b+c))/area is always greater than of equal to ? less than or equal to
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 6 months ago
View all Questions »